Vascular risk factors and morphometric data in cervical artery dissection: a case-control study. Issue 2 (16th January 2009) - Arnold, M; Pannier, B; Chabriat, H; Nedeltchev, K; Stapf, C; Buffon, F; Crassard, I; Thomas, F; Guize, L; Baumgartner, R W; Bousser, M-G
Abstract : Background: Limited knowledge exists on vascular risk factors, body height and weight in patients with spontaneous cervical artery dissection (sCAD). Patients and methods: In this case-control study, major vascular risk factors, body weight, body height and body mass index (BMI) of 239 patients obtained from a prospective hospital-based sCAD registry were compared with 516 age- and sex-matched healthy controls undergoing systematic health examinations in the Clinical and Preventive Investigations Center, Paris. Gender-specific analyses were performed. Results: The mean body height was higher in sCAD patients than in controls (171.3 cm (SD 8.6) vs 167.7 cm (8.9); p<0.0001) and sCAD patients had a significantly lower mean body weight (67.5 (12.2) kg vs 69.3 (14.6) kg; p<0.001) and mean BMI (22.9 (3.3) kg/m2 vs 24.5 (4.2) kg/m2 ; p<0.0001) than controls. The overall frequency of hypertension, diabetes, current smoking, past smoking and hypercholesterolaemia did not differ significantly between sCAD patients and controls. The mean total plasma cholesterol level was identical in both groups (5.5 mmol/l, SD 1.1). Gender specific subgroup analyses showed similar results for men and women. Conclusion: Patients with sCAD had a higher body height and a lower body weight and BMI than controls, while major vascular risk factors were similar in sCAD patients and controls.